1998
DOI: 10.1007/s004310050759
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis to sheep's milk cheese in a child unaffected by cow's milk protein allergy

Abstract: Sheep's milk and cheese derived from sheep's milk may cause severe allergic reactions in children affected and, as we report, in children not affected by cow's milk protein allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 10 publications
(12 reference statements)
0
10
0
1
Order By: Relevance
“…[97][98][99] Goat's and ewe's milks have also been implicated in anaphylactic reactions. 100,101 Unusual clinical presentations of CMA Unusual clinical presentations are as much a feature of CMA as one might expect from such a ubiquitous allergen source in food and the environment as milk (Box 1). [102][103][104][105][106][107][108][109][110][111][112] The natural history of CMA CMA is primarily of pediatric onset, [113][114][115] is generally outgrown, and is often the first stage of the ''allergic march.''…”
Section: Epidemiology Of Cmamentioning
confidence: 98%
“…[97][98][99] Goat's and ewe's milks have also been implicated in anaphylactic reactions. 100,101 Unusual clinical presentations of CMA Unusual clinical presentations are as much a feature of CMA as one might expect from such a ubiquitous allergen source in food and the environment as milk (Box 1). [102][103][104][105][106][107][108][109][110][111][112] The natural history of CMA CMA is primarily of pediatric onset, [113][114][115] is generally outgrown, and is often the first stage of the ''allergic march.''…”
Section: Epidemiology Of Cmamentioning
confidence: 98%
“…In those cases, the IgE binds the caseins (α S1 ‐, α S2 ‐, and β‐caseins) with high specificity and efficiency, but not to the whey proteins, despite their pronounced sequence homology (Ah‐Leung and others ). Several studies report the fact that patients with cow milk allergy have cross‐reactivity with sheep and goat milk, but not the reverse (Wüthrich and Johansson ; Calvani and others ; Umpierrez and others ; Muñoz‐Martín and others ; Viñas and others ). Nonetheless, the reason for this phenomenon is still unclear.…”
Section: Cross‐reactivity Of Milk Allergensmentioning
confidence: 99%
“…Its use has been reported that it could lead to anaphylactic reaction in children with CMA [18]. Goat milk seems to cross-react not only with cow milk proteins, but also with that of other mammalian milks such as sheep [1921]. In this aspect, goat milk seems to be as allergic as cow milk [5].…”
Section: Discussionmentioning
confidence: 99%